Asuhan Kebidanan Terintegrasi pada Ibu Hamil dengan Anemia untuk Mencegah Komplikasi Kehamilan - Rosmiarti, Rosmiarti; Apriliani, Indah (Penerbit Goodwood, 2025)
Purpose: Anemia in pregnancy is a significant health problem, with a prevalence reaching 37.1% in Indonesia. This case study aims to analyze midwifery care for pregnant women with anemia, focusing on Mrs. A, aged 30, at 28 weeks gestation. Method: This study used a descriptive case study approach involving interviews, observation, physical examination, and laboratory tests to collect comprehensive data on maternal condition and care interventions. Results: The findings show that Mrs. A experienced moderate anemia with hemoglobin levels of 8 g/dL, low blood pressure (90/60 mmHg), and suboptimal weight gain. Management included nutritional education, iron supplementation, and lifestyle modification. Conclusions: Holistic and evidence-based midwifery care is crucial in managing anemia during pregnancy, focusing on prevention and early treatment to improve maternal and fetal outcomes. Limitations: This study was limited to a single case and lacked long-term follow-up to evaluate changes in hemoglobin levels and pregnancy outcomes after intervention, limiting generalizability. Contribution: This study contributes to midwifery practice by demonstrating the importance of comprehensive, evidence-based care for managing anemia in pregnancy and underscores the need for continuous monitoring and nutritional education to prevent adverse outcomes.